Molecular characterization of circulating tumor cells in ovarian cancer - Kolostova, Katarina; Pinkas, Michael; Jakabova, Anna; Pospisilova, Eliska; Svobodova, Pavla; Spicka, Jan; Cegan, Martin; Matkowski, Rafal; Bobek, Vladimir (American journal of cancer research, 2016)
The main focus of the study was to detect circulating tumor cells (CTCs) in ovarian cancer (OC) patients using a new methodological approach (MetaCell(TM)) which is based on size-dependent separation of CTCs and subsequent cytomorphological evaluation. Cytomorphological evaluation using vital fluorescence microscopy approach enables to use the captured cells for further RNA/DNA analysis. The cytomorphological analysis is then completed by gene expression analysis (GEA). GEA showed that relative expression of EPCAM is elevated in CTC-enriched fractions in comparison to the whole peripheral blood sample and that the expression grows with in vitro cultivation time. Comparison of the relative gene expression level in the group of peripheral blood samples and CTC-fraction samples confirmed a statistically significant difference for the following genes (p < 0.02): KRT7, WT1, EPCAM, MUC16, MUC1, KRT18 and KRT19. Thus, we suggest that the combination of the above listed genes could confirm CTCs presence in OC patients with higher specificity than when GEA tests are performed for one marker only. The GEA revealed two separate clusters identifying patients with or without CTCs.
Keywords: cultivation; circulating tumor cells; in vitro; ovarian cancer; MetaCell; gene expression; CTCs